Genetic Susceptibility to Gestational Diabetes Mellitus in a Chinese Population - Cao, Minkai; Zhang, Le; Chen, Ting; Shi, Aiwu; Xie, Kaipeng; Li, Zhengying; Xu, Jianjuan; Chen, Zhong; Ji, Chenbo; Wen, Juan (Frontiers in Endocrinology, 2020)
Introduction: New genetic variants associated with susceptibility to obesity and metabolic diseases have been discovered in recent genome-wide association (GWA) studies. The aim of this study was to investigate the association of theses risk variants with gestational diabetes mellitus (GDM). Methods: We performed a case-control study including 964 unrelated pregnant women with GDM and 1,021 pregnant women with normal glucose tolerance (as controls). A total of 33 genetic variants confirmed by GWA studies for obesity and metabolic diseases were selected and measured. Results: We observed that FTO rs1121980 and KCNQ1 rs163182 conferred a decreased GDM risk in the dominant and additive model [additive model: OR(95%CI) = 0.79 (0.67-0.94), P = 0.007 for rs1121980; OR(95%CI) = 0.84 (0.73-0.96), P = 0.009 for rs163182], whereas MC4R rs12970134 and PROX1 rs340841 conferred an increased GDM risk in the dominant, recessive and additive model [additive model: OR(95%CI) = 1.25(1.07-1.46), P = 0.006 for rs12970134; OR(95%CI) = 1.22 (1.07-1.39), P = 0.002 for rs340841). With the increasing number of risk alleles of the four significant SNPs, GDM risk was significantly increased in a dose-dependent manner (P trend < 0.001). And the significant positive associations between the weighted genetic risk score and risk of GDM persisted. Further function annotation indicated that these four SNPs may fall on the functional elements of human pancreatic islets. The genotype-phenotype associations indicated that these SNPs may contribute to GDM by affecting the expression levels of their nearby or distant genes. Conclusion: Our study suggests that FTO rs1121980, KCNQ1 rs163182, MC4R rs12970134 and PROX1 rs340841 may be markers for susceptibility to GDM in a Chinese population.